Проблеми переходу розширень Chromium-based браузерів на Manifest V3 - Тяжельников, О. В. (ХНУРЕ, 2025)
This paper examines the challenges associated with the transition of Chromium-based browsers to Manifest V3. While the new standard aims to enhance security and performance, it introduces significant limitations for developers, particularly in content filtering and request management. The paper discusses the impact of restrictions on ad blockers, background processes, and dynamic script execution, highlighting the difficulties faced by developers and users alike. Additionally, the study analyzes responses from various browser vendors and potential future developments in browser extension policies.
Keywords: веб розширення; браузер Chromium; блокування реклами